Screening amaranth genotypes (Amaranthus spp.) for yield and resistance to leaf blight caused by Rhizoctonia solani Kuhn - Priya, V.P.=700 1 Celine, V.A.
(En, Fr, Es)
ilus., 9 ref.
Keywords: AMARANTHUS; GENOTIPOS; RESISTENCIA A LA ENFERMEDAD; RHIZOCTONIA SOLANI; INDIA